Comparison of noninvasive positive pressure ventilation with standard medical therapy in hypercapnic acute respiratory failure - KARAKURT, SAİT (ELSEVIER SCIENCE BV, 1998)
Study objective: To compare the efficacy of standard medical therapy (ST) and noninvasive mechanical ventilation additional to standard medical therapy in hypercapnic acute respiratory failure (HARF). Design: Single center, prospective, randomized, controlled study. Setting: Pulmonary medicine directed critical care unit in a university hospital. Patients: Between March 1993 and November 1996, 30 HARF patients were randomized to receive ST or noninvasive positive pressure ventilation (NPPV) in addition to ST. Interventions: NPPV was given with an air-cushioned face via a mechanical ventilator (Puritan Bennett 7200) with initial setting of 5 cm H2O continuous positive airway pressure and 15 cm H2O pressure support. Results: At the time of randomization, patients in the ST group had (mean +/- SD) Pao(2) of 54 +/- 13 mm Hg, Paco(2) of 67 +/- 11 mm Hg, pH of 7.28 +/- 0.02, and respiratory rate of 35.0 +/- 5.8 breaths/min. Patients in the NPPV group had Pao(2) of 55 +/- 14, Paco(2) of 69 +/- 15, PH of 7.27 +/- 0.07, and respiratory rate of 34.0 +/- 8.1 breaths/min. With ST, there was significant improvement of only respiratory rate (p < 0.05). However, with NPPV, Pao(2) (p < 0.001), Paco(2) (p < 0.001), pH(p < 0.001), and respiratory rate (p < 0.001) improved significantly compared with baseline. Sir; hours after randomization, pH (p < 0.01) and respiratory rate (p < 0.01) in NPPV patients were significantly bet-ter than with ST. Hospital stay for NPPV vs ST patients was, respectively, 11.7 +/- 3.5 and 14.6 +/- 4.7 days (p < 0.05). One patient in the NPPV group required invasive mechanical ventilation. The conditions of six patients in the ST group deteriorated and they were switched to NPPV; this was successful in four patients, two failures were invasively ventilated. Conclusion: This study suggests that early application of NPPV in HARF patients facilitates improvement, decreases need for invasive mechanical ventilation, and decreases the duration of hospitalization.
Keywords: acute respiratory failure; chronic obstructive pulmonary disease; hypercapnic acute respiratory failure; hypoxemia; intensive care unit; mechanical ventilation; noninvasive ventilation; OBSTRUCTIVE PULMONARY-DISEASE; MECHANICAL VENTILATION; FACE MASK; ACUTE EXACERBATIONS; AIRWAY PRESSURE; COPD PATIENTS; SUPPORT VENTILATION; IMMEDIATE; TRIAL